Diffusion limited precipitation of alumina in magnesium aluminate spinel. Issue 3 (7th November 2016) - Miller, Jesse Aaron; Reimanis, Ivar E.; Miao, Weiguo; Sutorik, Anthony C.
Abstract: Precipitation of Al2 O3 from nonstoichiometric, dense spinel was examined with the intent to design strengthened transparent ceramics. Powders of magnesium aluminate spinel, MgO· n Al2 O3, with compositions n= 1 and 2 were uniaxially hot‐pressed at 1873 K, hot isostatically pressed at 2073 K, and heat treated in air or vacuum at 1573 K for 1, 5, 10, 15, and 20 hour. It was observed that precipitation of α‐Al2 O3 in n= 2 material initiated from the surface and progressed to various depths, with greater depths corresponding to treatments in air. The kinetics are shown to be limited by the diffusion of oxygen through the reacted layer. The results reveal that the environment used to densify spinel has a large influence on the evolution of the two phase microstructure during subsequent heat treatment.